Factors underlying small medium enterprise development : the case of Sarawak - Suhaimi, hj Suhaili (2003)
This project draws upon material collected from qualitative corporative from interview and postal survey held with large and small company in Sarawak. It has also explored and gathered materials collected from biographies, articles and research paper from universities, agencies and organization. Drawing a conclusion after discussing the four underlying factors contributing to the growth of SMEs, is assumed that all the data from the survey and secondary resources will represent the whole of Sarawak growth and Malaysia as a general as no in-depth study has been made so far on this subject matter.